2018
DOI: 10.2471/blt.18.212167
|View full text |Cite
|
Sign up to set email alerts
|

Public health system integration of avoidable blindness screening and management, India

Abstract: In India, 73 million people have diabetes and 3.5 million infants are born preterm. Without timely screening, there is a risk of visual loss due to diabetic retinopathy and retinopathy of prematurity in these two groups, respectively. Both conditions are emerging causes of visual impairment in India but there is no public health programme for screening or management. Pilot projects were initiated in 2014 to integrate the screening and management of these conditions into existing public health systems, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…DRS also requires appropriate integration into routine care for sustainability [10]. It was shown that public health integration of DRS is a feasible strategy to control avoidable blindness [12]. As such, one feasible model of systematic DRS in LMICs could be screening of PwDM when they attend for routine medical care.…”
Section: Introductionmentioning
confidence: 99%
“…DRS also requires appropriate integration into routine care for sustainability [10]. It was shown that public health integration of DRS is a feasible strategy to control avoidable blindness [12]. As such, one feasible model of systematic DRS in LMICs could be screening of PwDM when they attend for routine medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Screening was integrated into sick new-born care units at the district level and treatment facilities were provided and improved at the closest publicly funded medical schools. In the first two years, there were substantial improvements in awareness, screening, treatment and partnership between stakeholders, and changes in public health policy (Gudlavalleti et al, 2018). Other strategies which are being currently used include training members of the neonatal team to capture retinal images using wide-field imaging which are then read by ROP experts.…”
Section: Discussionmentioning
confidence: 99%
“…In the first two years, there were substantial improvements in awareness, screening, treatment and partnership between stakeholders, and changes in public health policy. [22] Other strategies which are being currently used include training members of the neonatal team to capture retinal images using wide-field imaging which are then read by ROP experts. A KIDROP like screening model can provide ROP screening in low-resource settings, remote centres, and regions with few ROP specialists.…”
Section: Discussionmentioning
confidence: 99%